Pensiones para personas con discapacidad en Colombia1 (2019)
In Colombia, the right to a pension, in any modality, is one of the mechanisms for guaranteeing the right to social security. In order to determine which pension regimes are more suited to the social and labor reality of the country’s people with disabilities, Colombian legislation and jurisprudence were reviewed through an exploratory-descriptive study method. It was found that this right gives special treatment to that population. Colombian legislation regulates at least ten kinds of pensions for this group of people with special constitutional protection.